Rottenberg and the economics of sport after 50 years: an evaluation - Peter J. Sloane (Institute for the Study of Labor (IZA), 2006)
Simon Rottenberg's seminal 1956 article in the Journal of Political Economy, 1956, is generally accepted as the starting point for the development of the economics of sport. While he recognised that certain features of professional sports leagues were unusual he saw little reason to treat this industry any differently from a conventional industry. He discusses the importance of uncertainty of outcome, the monopsonistic nature of the labour market, the nature of the product and demand (attendances). He considers alternatives to the reserve clause, such as equal revenue sharing, maximum salary limits, equal market franchise distribution and roster limits. Each of these is rejected in favour of a free market solution which, on the basis of the invariance principle, he suggests will perform just as well as the reserve clause in allocating talent to where it is most productive. The ensuing literature has focused on all these issues, many of which have created considerable debate amongst sports economists. In particular the assumption of profit maximisation has been challenged and a divergence of views, reflected in the so-called North American and European models of sports leagues has emerged. Over the last 50 years sports leagues have expanded, TV markets have opened up and legal challenges to existing practices have multiplied. This paper seeks to evaluate Rottenberg's contribution to a rapidly expanding field and to judge its relevance today.
Keywords: J0; L0; L8; 330; sport; monopsony; monopoly power